2022
DOI: 10.1155/2022/3156785
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology and Molecular Docking Analysis Explores the Mechanisms of Cordyceps sinensis in the Treatment of Oral Lichen Planus

Abstract: Objective. Oral lichen planus (OLP) is the most common potentially malignant disorder of the oral cavity. This study aimed to investigate the mechanism of action of Cordyceps sinensis in the treatment of OLP and provides a theoretical support for improving current treatment regimens for OLP. Methods. The active components and therapeutic targets of Cordyceps sinensis were predicted and screened using the TCMSP, SymMap, PubMed, HIT 2.0, and PharmMapper databases, while the relevant OLP targets were predicted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 62 publications
0
5
1
Order By: Relevance
“…In a recent study by Ma et al [ 18 ] in 2022, among 52 possible targets, TNF, IL-6, CD4, EGFR, IL1B, IL10, AKT1, VEGFA, TP53, and IL2 had the highest degree values, indicating that these targets are important in the development of OLP and are expected to be targeted for clinical treatment of OLP. They also recommended that Cordyceps sinensis as a traditional Chinese medicine could be a beneficial choice in the OLP treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study by Ma et al [ 18 ] in 2022, among 52 possible targets, TNF, IL-6, CD4, EGFR, IL1B, IL10, AKT1, VEGFA, TP53, and IL2 had the highest degree values, indicating that these targets are important in the development of OLP and are expected to be targeted for clinical treatment of OLP. They also recommended that Cordyceps sinensis as a traditional Chinese medicine could be a beneficial choice in the OLP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al [ 18 ] in 2022 described that EGFR is one of the most important targets in the development of OLP. Some studies showed overexpression of EGFR in OSCC [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 2D files of small molecule ligands were downloaded by querying the PubChem database (https://pubchem.ncbi.nlm.nih.gov/), [28] and the ligand formats were optimized and converted to 3D structures by ChemBio3D 14.0.0 software.The PDB format files of the receptors were obtained by downloading from the Uniprot database (https://www.uniprot.org/) and the PDB database (http://www1.rcsb.org/), and the receptors were de-hydrogenated and de-residualized using PyMOL 2.4 software (https://pymol.org/2/). [29–31] Use AutoDockTools 1. 5.…”
Section: Methodsmentioning
confidence: 99%
“…The PDB format files of the receptors were obtained by downloading from the Uniprot database (https://www.uniprot.org/) and the PDB database (http://www1.rcsb.org/), and the receptors were de-hydrogenated and de-residualized using PyMOL 2.4 software (https://pymol.org/2/). [29][30][31] Use AutoDockTools 1. 5.…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…The PPI network le was then loaded into the Cytoscape software for visualization, and the "CytoHubba" plug-in was used to calculate three topological parameters including Degree Centrality (DC), Closeness Centrality (CC), and Betweenness Centrality (BC) [33] . These three topological parameters, a higher value represents greater importance of the node in the merged network [34] . Subsequently, these screened hub genes were imported into the Cytoscape software, and constructed the PPI core sub network.…”
Section: Ppi Network and Core Sub Networkmentioning
confidence: 99%